Religiosity and the motivation for social affiliation. (15th July 2017) - Van Cappellen, Patty; Fredrickson, Barbara L.; Saroglou, Vassilis; Corneille, Olivier
Abstract: Although universal, the motivation to affiliate can vary as a function of individual differences and of the characteristics of the target. Three studies explored the extent to which religious beliefs and identity are related to social affiliation motivation. Because most religions advocate affiliation and provide opportunities for frequent experiences of affiliation, we reasoned that religious people might show greater affiliation motivation in everyday attitudes and behaviors. We found that religiosity was positively related to implicit and behavioral measures of general social affiliation (Studies 1 and 2). However, manipulating the identity of the affiliation target revealed that when affiliating might not lead to positive outcomes, the relation between religiosity and social affiliation disappeared (but did not reverse). In Studies 2 and 3, when the target of the affiliation was explicitly identified as a member of a threatening out-group (atheist), religiosity did not predict affiliation behaviors. We discuss the mechanisms by which religiosity motivates and constrains social affiliation and the potential implications for social influence and intergroup processes. Highlights: The universal social affiliation motive varies across people. Individual differences in religiosity predict greater implicit and behavioral affiliation. This effect is moderated by the religious identity of the target of affiliation. Religiosity does not predict affiliation when the target is value-threatening.